PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK FASE E DI SMAN 3 BUKITTINGGI - Calista, Fionda Febrila (Departemen Matematika, 2023)
One of the things that is very crucial for students is having a good learning outcomes. However, the reality low learning outcomes are often found in mathematics learning. Such as Phase E students at SMAN 3 Bukittinggi whose mathematics learning achievements remain relatively modest. In this case, Two Stay Two Stray (TSTS) is the solution. The objective of this case is to examine the disparities in mathematics learning results between students who were educated using the TSTS type cooperative learning strategy and those who were educated using comventional learning models in Phase E of SMAN 3 Bukittinggi. This type of study is a quasy experiment and a nonequivalent post-test only control group research design. The populace of this study were Phase E students of SMAN 3 Bukittinggi. The sampling method employed in this case is Simple Random Sampling, resulting in class X.E.4 being selected as the ecperimental group and class X.E.9 as the control group the acquisition of data in the research is conducted using a final test in the form of a learning achievement test which was analyzed by the t test. The finding of the research analysis on the results of the final test with the help of Minitab software, obtained P-value = 0.001 at a significant level of a = 0.05, this indicates that the students who implemented the TSTS type cooperative learning model achieved betted learning achievements compared to the students who studied using conventional learning in Phase E of SMAN 3 Bukittinggi. Thus, based on the research findings, it can be gathered that the implementation of the TSTS cooperative learning strategy significantly influenced the student performance of Phase E students at SMAN 3 Bukittinggi.Keywords – Two Stay Two Stray, Learning Outcomes